(untitled) (Raparin Journal of Humanities (RJH), 2025)
This paper entitled " Delexical Verbs in English and Kurdish Language: A Comparative Study" is an attempt to compare both languages related to delexical verbs in terms of syntax and semantics. Delexical verbs, a set of common and frequent verbs, are the indication of an important group of transitive verbs in English language which take a core role in spoken and written language. This study hypothesized that there are several similarities and differences regarding delexical verbs in both languages. Delexical verbs have a unique structure in which the lexical verb is delexicalised, and some changes occur in the nature of the verb, especially on its meaning. The meaning of the action is shifted from the verb into the accompanied noun. The aim of this study is to make a comparative analysis of delexical verbs in English and Central Kurdish languages to find out the similarities and differences of delexical verbs between English and Kurdish (Central Kurdish).